SiLaC® with EPSiT®: early outcomes of laser-endoscopic therapy for pilonidal sinus - Ouali, Mustapha (Frontiers in Surgery, 2025)
BackgroundPilonidal sinus disease (PSD) commonly affects young adults and often requires repeated interventions with prolonged healing times. We evaluated a combined approach using Sinus Laser Ablation of the Cyst (SiLaC®) and Endoscopic Pilonidal Sinus Treatment (EPSiT®) to investigate postoperative pain, healing time, and recurrence.MethodsThis retrospective, single-center study included 83 patients (aged 15–50) treated from January 2021 to December 2023 at Proctolaser Clinic, Tunisia. Under local, regional, or general anesthesia, patients underwent endoscopic debridement (EPSiT®) followed by diode laser ablation (SiLaC®) of sinus tracts. Data on operative time, Visual Analogue Scale (VAS) pain score, healing time to complete epithelialization, recurrence, and time to return to work were collected. All patients had at least 6 months of follow-up; a subset was followed up to 1 year.ResultsThe mean operative time was 25 ± 5.4 min. Mean VAS pain score at 24 h was 1.2 ± 0.6, and 92.3% of patients resumed work or normal activities within 24 h. Mean healing time was 17.3 days, with 95% achieving complete epithelialization by 3 weeks. The overall recurrence rate at 6 months was 3.6% (3/83). Two recurrences (3.3%) occurred in patients with primary PSD, and one recurrence (4.3%) occurred in a patient with recurrent PSD. Minor infections occurred in 1.2% (1/83) of patients and resolved with oral antibiotics. Aesthetic satisfaction was high; 88% rated outcomes “excellent.”ConclusionsCombining SiLaC® with EPSiT® for pilonidal sinus disease appears safe and effective, featuring minimal pain, rapid return to daily activities, low recurrence, and excellent cosmetic results. A longer-term, multicenter approach is recommended to confirm durability and cost-effectiveness.